Globalization for woman in third world country - Sorayya, Khansa (2013)
The extreme of globalization era bring woman in third world country into unpleasant place, where system in society still strong and hard for woman to survive not only their live but also their family as well. In this paper I try to reveal the condition of woman in third world country from economic perspective, before globalization and after globalization. Does globalization make easier to woman get their position in public area or vice versa?